SPORT: Does incidental durotomy affect long-term outcomes in cases of Spinal Stenosis? - Desai, Atman (Neurosurgery, 2011)
BACKGROUND: Incidental durotomy is a familiar encounter during surgery for lumbar spinal stenosis. The impact of durotomy on long-term outcomes remains a matter of debate. OBJECTIVE: To determine the impact of durotomy on the long-term outcomes of patients in the Spine Patient Outcomes Research Trial (SPORT). METHODS: SPORT cohort participants with a confirmed diagnosis of spinal stenosis (SPS), without associated spondylolisthesis, undergoing standard, first-time, open decompressive laminectomy, with or without fusion, were followed from baseline at 6 weeks, and 3, 6, 12 months and yearly thereafter, at 13 spine clinics in 11 US states. Patient data from this prospectively gathered database was reviewed. As of May 2009, the mean follow-up among all analyzed patients was 43.8 months. RESULTS: 409 patients underwent first-time open laminectomy with or without fusion. 37 (9%) of these patients had an incidental durotomy. No significant differences were observed with or without durotomy in age, sex, race, body mass index, the prevalence of smoking, diabetes and hypertension, decompression level, number of levels decompressed, or whether or not an additional fusion was performed. The durotomy group had significantly increased operative duration, operative blood loss and inpatient stay. There were however, no differences in incidence of nerve root injury, mortality, additional surgeries, primary outcomes (SF-36 scores of body pain or physical function, or Oswestry disability index) at yearly follow ups to 4 years. CONCLUSIONS: Incidental durotomy during first time lumbar laminectomy for spinal stenosis did not impact long-term outcomes in affected patients.